Coupled chemical reactions in dynamic nanometric confinement: IX. Etched tracks with membranes made of calcium carbonate. Issue 1 (2nd January 2020) - Vacik, J.; Hnatowicz, V.; Fink, D.; Hernandez, G. Muñoz; Arellano, H. García; Kiv, A.; Alfonta, L.
Abstract : In the recent papers of this series the formation and characterisation of Ag2 O and LiF membranes within etched swift heavy ion tracks in thin polymer foils by the 'Coupled Chemical Reaction' (CCR) approach was described. Such membrane-containing etched tracks were shown to be useful to create enzyme-clad biosensors of optimum efficiency. Some planned biosensors of higher complexity would, however, require the re-dissolution of the membranes after the enzyme deposition step, without affecting the enzyme's performance. To accomplish this, we looked for membrane materials that could, on the one hand, be easily produced by the CCR strategy, but on the other hand, be also easily re-dissolved thereafter in a bio-friendly way. As we think that earth alkali carbonates would fulfil these requirements (they dissolve already in very weak organic acids), we studied here the formation of membranes of Calcium carbonate. Interestingly it turned out that their membrane formation mechanism differs somewhat from that of the previously studied systems. Their basic 'fingerprints' are stable capacitive current responses – rather than the 'quiet phases' during else highly agitated spiky Ohmic current responses, as was observed for the earlier studied membrane materials Ag2 O and LiF.